Somatic mosaic deletions involving SCN1A cause Dravet syndrome. Issue 3 (17th January 2018) - Nakayama, Tojo; Ishii, Atsushi; Yoshida, Takeshi; Nasu, Hirosato; Shimojima, Keiko; Yamamoto, Toshiyuki; Kure, Shigeo; Hirose, Shinichi
Abstract : Somatic mosaicism in single nucleotide variants of SCN1A is known to occur in a subset of parents of children with Dravet syndrome (DS). Here, we report recurrent somatic mosaic microdeletions involving SCN1A in children diagnosed with DS. Through the evaluation of 237 affected individuals with DS who did not show SCN1A or PCHD19 mutations in prior sequencing analyzes, we identified two children with mosaic microdeletions covering the entire SCN1A region. The allele frequency of the mosaic deletions estimated by multiplex ligation‐dependent probe amplification and array comparative genomic hybridization was 25–40%, which was comparable to the mosaic ratio in lymphocytes and buccal mucosa cells observed by fluorescence in situ hybridization analysis. The minimal prevalence of SCN1A mosaic deletion is estimated to be 0.9% (95% confidence level: 0.11–3.11%) of DS with negative for SCN1A and PCDH19 mutations. This study reinforces the importance of somatic mosaicism caused by copy number variations in disease‐causing genes, and provides an alternative spectrum of SCN1A mutations causative of DS. Somatic deletions in SCN1A should be considered in cases with DS when standard screenings for SCN1A mutations are apparently negative for mutations.